2009
DOI: 10.1152/ajprenal.90649.2008
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine attenuates inflammatory cell infiltration and extracellular matrix accumulation in diabetic nephropathy

Abstract: Recent studies have demonstrated that an inflammatory mechanism contributes to the pathogenesis of diabetic nephropathy (DN). It is also known that colchicine (Col) can prevent various renal injuries via its anti-inflammatory action. However, the effect of colchicine on DN has never been explored. This study was undertaken to elucidate the effect of colchicine on inflammation and extracellular matrix accumulation in DN. In vivo, 64 rats were injected with diluent (C; n = 32) or streptozotocin intraperitoneally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 47 publications
2
51
1
Order By: Relevance
“…51 Lower expression of MCP-1 and intercellular adhesion molecule-1 as pro-inflammatory proteins led to reduced infiltration of inflammatory cells, and an accompanying reduction in ECM accumulation. 52 Moreover, cytokines are known to be sequestered in the ECM and can be released by MMPs. 53 The correlation between ECM and inflammatory proteins may be of importance in thickened BM as observed in both types of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…51 Lower expression of MCP-1 and intercellular adhesion molecule-1 as pro-inflammatory proteins led to reduced infiltration of inflammatory cells, and an accompanying reduction in ECM accumulation. 52 Moreover, cytokines are known to be sequestered in the ECM and can be released by MMPs. 53 The correlation between ECM and inflammatory proteins may be of importance in thickened BM as observed in both types of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent experimental study, colchicine administration to streptozotocin-induced diabetic rats significantly reduced UAE, inflammatory cell infiltration and extracellular matrix accumulation. These beneficial effects were associated with inhibition of inflammatory molecules expression in the renal tissue, including ICAM-1 [102] .…”
Section: Intercellular Adhesion Molecule-1mentioning
confidence: 98%
“…MC proliferation is commonly observed in a variety of pathological changes in glomerular injury. It has been demonstrated that MC dysfunction, including overproliferation and an increase in ECM production [3,4] , is implicated in the development of DN [5,6] . Hyperglycemia has been well documented as an independent risk factor for DM-induced complications.…”
Section: Introductionmentioning
confidence: 99%